Incorporation of Chromate into Calcium Carbonate Structure During Coprecipitation - Hua, Bin; Deng, Baolin; Thornton, Edward C; Yang, John; Amonette, James E (Water, air, and soil pollution, 2007)
To rigorously assess treatment technologies and establish regulatory framework for chromate-contaminated site remediation, it is useful to know the exact chromium speciation in soil matrices. In an earlier study, Thornton, E. C., & Amonette, J. E. (1999). Hydrogen sulfide gas treatment of Cr(VI)-contaminated sediment samples from a plating-waste disposal site - implications for in-situ remediation. Environmental Science & Technology, 33, 4096-4101, reported that some chromate in the bulk particles was not accessible to gaseous reductants or solution-phase extractants, based on XANES studies. We hypothesized that part of this non-extractable chromate may reside in the structure of minerals such as calcium carbonate. To test this hypothesis, a number of calcium carbonate precipitates were prepared in the presence of various concentrations of chromate during the precipitation, which could coprecipitate chromate, or by adding chromate after the precipitation was completed. Hydrochloric acid was used to dissolve calcium carbonate and therefore extract the coprecipitated and surface attached chromate. The results showed that the coprecipitated chromate was non-extractable by hot alkaline solution or phosphate buffer, but could be solubilized by HCl in proportional to the amount of calcium carbonate dissolved. The X-ray diffraction experiments revealed that the coprecipitation of chromate with calcium carbonate had an influence on its crystal structure: The higher the chromate concentration, the greater the ratio of vaterite to calcite.